Pebisnis Islam dan Muslim Kelas Menengah ke Atas di Indonesia: Kesalehan, Gaya Hidup, dan Pasar - Triantoro , Dony Arung (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2020)
The discussion regarding middle and upper class Muslims in Indonesia has become an interesting study among scholars with different focus of study. The reason is because middle and upper class Muslims continue to move dynamically and play an important role in the socio-religious landscape in Indonesia. This paper seeks to explain the global discourse that has initiated the emergence of a new lifestyle among middle and upper class Muslims in Indonesia. The purpose of this study is to analyze the phenomenon that develops both offline and online. Islamic expressions displayed by middle and upper class Muslims in Indonesia show the intersection of piety, lifestyle, and the market. The theory used in this study is the constructivism paradigm, phenomenology, and virtual communication. The method used is a phenomenological approach through observation from 2018 to early 2020, on business actors in Yogyakarta and Pekanbaru. The results of the analysis of this study argue that the increasing expression of Islam among middle and upper class Muslims has in turn initiated the emergence of Islamic business actors who facilitate the new lifestyle of upper middle class Muslims.